Potential Nature Objects In District of Pasaman Pasaman Barat Region - FITRI, LISDA; DRS. Bakaruddin, Ms, DRS. Bakaruddin, Ms; SE, M.Si, Nefilinda (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ Â Â Inventory of all the potential that exists in each of attractions such as Accessibility to reach tourist destinations (DTW), accommodation, tourist attractions, and facilities needed in inventarisasikan in writing. This study aims to determine the potential of Natural Attraction In Pasaman District Pasaman Barat Region. Type used was qualitative using observation techniques, interviews, documentation. Informants in this study was taken snowball sampling. Key informants taken the Tourism Office of Pasaman Barat, village trustee, and visitors. Data analysis used the analysis of the primary data analysis and secondary data analysis. The study found: 1) accessibility of attractions in Pasaman district include substandard, especially the waterfall of Siburai â Burai attraction, because they are too distant from roads and difficult terrain. While the accessibility of attractions including the Ikan Larangan Lubuak Landua good, but there is no public transport available to the attraction, 2) Existing facilities at attractions in Pasaman district include less, especially at attractions of Siburai â Burai waterfall, because the location of attractions is so far. Supporting facilities for fish attraction in Ikan Larangan Lubuk Landua including good, 3) Infrastructure of attractions supporting in Pasaman District, infrastructure in attractions Siburai â Burai waterfall and attraction Ikan Larangan Lubuk Landua including prohibition either. Only it was a little far away from each attraction, which is in the center of town and 4) The appeal in the attractions of Pasaman District, waterfall attractions including Siburai - Burai are very interesting, because it has clean air and challenging terrain to serve as hiking and trecking arena, while the prohibition of fish attraction Ikan Larangan Lubuak Landua including interesting historical sideÂ